Consumer adoption of fashion rental for sustainable consumption: a systematic literature review and integrative framework - Song, Mingli; Xu, Yanni; Senathirajah, Abdul Rahman bin S.; Yan, Xiang (Frontiers in Sustainability, 2025)
IntroductionFashion rental is advanced as a pathway for the circular economy that addresses sustainability concerns while meeting demand for fashion variety, yet the evidence base on consumer adoption remains fragmented. This study synthesizes prior research and develops an integrative conceptual framework for why and how consumers adopt fashion rental.MethodsWe conducted a systematic literature review of 68 peer-reviewed articles indexed in Web of Science and Scopus and published between 2015 and 2024. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, studies were screened, selected, and thematically synthesized to map the state of knowledge and to construct an integrative Stimulus–Organism–Response framework.ResultsResearch output has risen rapidly since 2019, with a concentration in sustainability and consumer behavior journals and a geographic focus on the United States and China. The synthesis identifies three categories of external stimuli (product attributes; platform design and service features; marketing and social cues), three types of internal psychological processes (cognitive appraisal; emotional responses; normative considerations), and two forms of behavioral outcomes (intentions; actual behaviors). The relationships from external stimuli to internal processes and onward to behavioral outcomes are significantly moderated by demographic characteristics, psychological traits, and situational factors.DiscussionThe review consolidates a fragmented literature and proposes an integrative Stimulus–Organism–Response framework that offers a more nuanced foundation than prior models by holistically incorporating external cues, a fuller spectrum of consumer psychology, and critical moderating variables. The framework advances theoretical understanding and provides actionable guidance for the design and management of fashion rental platforms, while limitations related to English-language coverage and the exclusion of grey and non-English sources are acknowledged.